Differences in Rhizosphere Microbial Community Structure and Composition in Resistance and Susceptible Wheat to Fusarium Head Blight - Li, Han; Tang, Mingshuang; Zheng, Tao; Yang, Ming; Wang, Youning; Shuai, Yating; Li, Yan; Zhang, Yibo; Ma, Dongfang (Cellular Microbiology, 2023)
Fusarium head blight (FHB) is a serious disease of wheat that threatens wheat production worldwide. In this study, high-throughput sequencing technology was used to analyze the rhizosphere soil microbial metagenomes of 4 wheat cultivars with different levels of resistance to FHB. The results showed that there were differences in the diversity, structure, and composition of rhizosphere microorganisms between resistant and sensitive varieties. The rhizosphere soil bacterial diversity of the resistant wheat varieties Su Mai 3 and Yang Mai 16 was higher than that of the susceptible wheat varieties Zheng Mai 9023 and Zhou Mai 20. The diversity of rhizosphere fungi in resistant varieties was lower than that in susceptible varieties, but the abundance was higher than that in susceptible varieties. Variety was found to alter the community structure of wheat rhizosphere microorganisms. Resistant varieties SM3 and YM16 and moderately susceptible variety ZM9023 had similar microbial community structure, while highly susceptible variety ZM20 was significantly different from other varieties. The study is aimed at analyzing the effects of wheat varieties of different resistance to FHB on the composition and abundance of rhizosphere soil microbial community to screen out bacteria or fungi that can be used to control FHB, providing the theoretical basis for FHB biological control.